Pesan Kesadaran Sosial dalam Lirik Lagu Taylor Swift “Mean” - Tanoto, Olivia; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Low social awareness can lead to bullying, which has a negative impact on individuals. Therefore, social awareness is essential to prevent bullying. Social awareness can be raised through various media, like song lyrics. Lyrics containing messages of social awareness can be used to grow social awareness on society. Song lyrics are a form of mass communication that can convey messages to a wide audience. Through lyrics, songs can deliver various messages, including those related to social awareness. This research aims to identify and describe the representation of social awareness messages in the lyrics of the song